Feminism as Islamophobia: can western feminism be replicated in Muslim society? - Hasan, Md. Mahmudul (2011)
One treasonous use of feminism is to misappropriate it to advance colonial interests and to support imperialist wars of occupation that repress subjugated people including women and children. Another is to use it to stigmatize a particular religion, Islam, even though, compared to other world religions, its treatment of women is arguably preferable and more enlightened. In this article, I argue that ignorance about, and prejudice against, Islam contribute to portraying it as a misogynistic creed. Wrong notions of Islam lead feminists in Muslim societies to denigrate Islamic teachings and borrow western ideas to advance women’s causes. Lampooning Islam and replicating western feminist ideas in Muslim lands have served neither women nor feminism. Such feminist tendencies rather give a bad name to the women’s rights movement and fuel controversy, anger and resentment of Muslims.